Clinical characteristics and outcome of infective endocarditis in adults with bicuspid aortic valves: a multicentre observational study. Issue 21 (16th May 2010) - Tribouilloy, C; Rusinaru, D; Sorel, C; Thuny, F; Casalta, J-P; Riberi, A; Jeu, A; Gouriet, F; Collart, F; Caus, T; Raoult, D; Habib, G
Abstract : Objective: To analyse characteristics and outcomes of infective endocarditis (IE) on bicuspid aortic valves (BAV) and to compare the risk of death according to the presence or absence of BAV. Design: 5-year observational study. Setting: Population of 856 patients with definite IE according to the Duke criteria from two tertiary centres (Amiens and Marseille, France). Patients: 310 consecutive patients with definite native aortic valve IE enrolled between 1991 and 2007. Interventions: Patients underwent transthoracic and transoesophageal echocardiography during hospitalisation. Surgery was performed on a case-by-case basis according to conventional guidelines. Main outcome measures: In-hospital mortality and 5-year overall mortality. Results: Patients with BAV IE (n=50, 16%) were younger, had fewer comorbidities and a higher frequency of aortic perivalvular abscess (50%). Presence of BAV (OR 3.79 (1.97–7.28); p<0.001) was independently predictive of abscess formation. Early surgery was performed in 36 BAV patients (72%) with a peri-operative mortality of 8.3%, comparable to that of patients with tricuspid aortic valve IE (p=0.89). BAV was not independently predictive of in-hospital mortality (OR 0.89 (0.28–2.85); p=0.84) or 5-year survival (HR 0.71 (0.37–1.36); p=0.30). Age, comorbidities, heart failure, Staphylococcus aureus and uncontrolled infection were associated with increased 5-year mortality in BAV patients. Conclusion: BAV is frequent in adults with native aortic valve IE. Patients with BAV IE incur high risk of abscess formation and require early surgery in almost three-quarters of cases. IE is a severe complication in the setting of BAV and warrants prompt diagnosis and treatment.